2018
DOI: 10.1016/j.actpsy.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

My true face: Unmasking one's own face representation

Abstract: Face recognition has been the focus of multiple studies, but little is still known on how we represent the structure of one's own face. Most of the studies have focused on the topic of visual and haptic face recognition, but the metric representation of different features of one's own face is relatively unknown. We investigated the metric representation of the face in young adults by developing a proprioceptive pointing task to locate face landmarks in the first-person perspective. Our data revealed a large ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 35 publications
4
33
1
Order By: Relevance
“…By introducing visual feedback and enabling pointing by visuo-motor control, purely proprioceptive-based face topography cannot be evaluated; however, the main research question in the present study was whether young children can maintain their motivation for task repetition. Therefore, a direct comparison with the Mora et al (2018) findings is a task for the future. However, if we can sophisticate our task to distinguish visuo-motor control and measure the mistouched points in more detail, we will be able to quantify the distortion of the face topography.…”
Section: Summary and Future Directionsmentioning
confidence: 96%
See 3 more Smart Citations
“…By introducing visual feedback and enabling pointing by visuo-motor control, purely proprioceptive-based face topography cannot be evaluated; however, the main research question in the present study was whether young children can maintain their motivation for task repetition. Therefore, a direct comparison with the Mora et al (2018) findings is a task for the future. However, if we can sophisticate our task to distinguish visuo-motor control and measure the mistouched points in more detail, we will be able to quantify the distortion of the face topography.…”
Section: Summary and Future Directionsmentioning
confidence: 96%
“…How can the findings of the present study be considered in adult studies of face topography? As stated above, in Mora et al (2018) study, adult participants were asked to point to 11 face landmarks (i.e., hairline, corners of each eye, tip of nose, lateral side of both nostrils, corners of the mouth, and chin). The results showed overestimated of the width of the nose and mouth (Mora et al, 2018).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample size was determined by an a priori power analysis run with G* Power (Faul, Erdfelder, Buchner & Lang, 2009), which considered the type of analyses required to assess: i) differences between real and represented body measures by means of t-tests; and ii) differences between represented body measures among different conditions by means of analysis of variance. We also considered previous studies on body representation adopting a localization task that reported an averaged effect size for one sample t-test of 0.8 (i.e., Ganea & Longo, 2017;Mora, Cowie, Banissy & Cocchini, 2018).…”
Section: Participantsmentioning
confidence: 99%